2016
DOI: 10.1371/journal.pmed.1002076
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Recreational and Commuter Cycling, Changes in Cycling, and Type 2 Diabetes Risk: A Cohort Study of Danish Men and Women

Abstract: BackgroundCycling is a recreational activity and mode of commuting with substantial potential to improve public health in many countries around the world. The aim of this study was to examine prospective associations between recreational and commuter cycling, changes in cycling habits, and risk of type 2 diabetes (T2D) in Danish adults from the Diet, Cancer and Health cohort study.Methods and FindingsAt baseline from 1993 to 1997, 24,623 men and 27,890 women from Denmark, 50–65 y of age and free of T2D and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…A study in Chinese women and a study conducted among Danish men and women each reported bicycling to work and for other reasons being inversely associated with the risk of all‐cause mortality compared with passive travel. Another recent published study of Danish middle‐aged and older adults reports that bicycling to work is related to lower risk of type 2 diabetes mellitus . In a Dutch cohort study, engagement in nonspecific bicycling was associated with lower risk of cardiovascular disease .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A study in Chinese women and a study conducted among Danish men and women each reported bicycling to work and for other reasons being inversely associated with the risk of all‐cause mortality compared with passive travel. Another recent published study of Danish middle‐aged and older adults reports that bicycling to work is related to lower risk of type 2 diabetes mellitus . In a Dutch cohort study, engagement in nonspecific bicycling was associated with lower risk of cardiovascular disease .…”
Section: Discussionmentioning
confidence: 94%
“…Another recent published study of Danish middle-aged and older adults reports that bicycling to work is related to lower risk of type 2 diabetes mellitus. 22 In a Dutch cohort study, engagement in nonspecific bicycling was associated with lower risk of cardiovascular disease. 23 Furthermore, in a nested case-control study, we have previously reported that compared with bicycling to work, commuting by car was associated with greater risk of myocardial infarction, 24 and this relationship was to a large extent explained by inflammatory and hemostatic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced car use due to active commuting can lead to a decrease in air pollution and traffic congestion, and more efficient use of urban land due to a reduction in parking lots [2][3][4]. Moreover, active commuting has several health benefits, including increasing physical activity [5] and promoting mental health [6][7][8], and reducing obesity [9], cardiovascular diseases [10][11][12], type 2 diabetes [13], cancers [10,12], and all-cause mortality [10,14,15]. Avila-Palencia et al have examined the relationship between bicycle commuters and perceived stress in Barcelona, Spain.…”
Section: Introductionmentioning
confidence: 99%
“…They conducted their studies in Danish adults and collected data from the prospective cohort study, "Diet, Cancer, and Health". They found that cycling was associated with lower risks of coronary heart disease [11] and type 2 diabetes [13]. Andersen and colleagues have also focused on cycling as active commuting in Copenhagen, Denmark, and found cycling to work was associated with a lower risk of mortality [14].…”
Section: Introductionmentioning
confidence: 99%
“…2 Since then, many studies have consistently reported lower rates of cardiovascular disease, 3 4 type 2 diabetes, 5 cancers, 4 and mortality 6 associated with cycling compared with not cycling. Other studies have shown that walking is also associated with health benefits, including a lower risk of cardiovascular disease, type 2 diabetes, and all cause mortality.…”
mentioning
confidence: 99%